Combined approach using morphology and ITS-sequences for description of three new species of Macrocheles (Acari: Macrochelidae) - Niogret, Jerome; Nicot, Antoine (Zootaxa, 2008)
Three new phoretic mites from France and Gabon are described. Macrocheles lumareti sp. nov. (from France) was collected on Copris lunaris (Coleoptera, Scarabaeidae). Both M. bertrandi sp. nov. and M. ovoidalis sp. nov. (from Gabon) were collected on Stomoxys calcitrans (Diptera). On the basis of morphological characteristics, M. lumareti and M. bertrandi were identified as belonging to the M. glaber and M. muscadomesticae groups respectively. Genetic analyses using an ITS marker confirmed that M. lumareti belongs to the M. glaber-group s. str., more closely related to M. glaber than all other species. The analysis did not support M. bertrandi as a member of the M. muscaedomesticae group. The third species, M. ovoidalis, using both morphological and genetical markers, appeared clearly isolated from all other known Macrocheles species.